The Status of the German Language in Modern Germany: a Brief Description of the Language Policy in the Federal Republic of Germany - E. S. Alekseenko (Дискурс)
Introduction.  This  article  is  devoted  to  the  modern  language  policy  in  Germany.  An analysis of intra- and extra-linguistic factors  that influence  the steps  taken by the state  in relation  to  the  languages  spoken  on  the  territory  of  the  country  makes  it possible  to characterize the  position  and  status  of  the  language  of  the  titular  nation  in Germany. Consideration   of   the   current   situation   can   help   to   draw  a   conclusion   about   the effectiveness   of   the    implemented    language   policy,   suggest    further    ways   of   the development  of the German  language, and also understand  the underlying causes  of the evolution of the language and its current state.Methodology and sources. The article is based  on the results  of the analysis of modern studies  of  the  role,  status  and  specifics  of  the  German  language  by such  linguists and philologists as Yu.V. Kobenko, S.A. Zhilyuk, V.I. Kozhevnikova, A. Kirkness, W. Hendelmeier, as well as the analysis of the main laws and legal acts in Germany regulating its language policy. For a more  complete  description  of the  studied  phenomenon, the  classic  works of N.B. Vakhtin, E.V. Golovko, A.D. Schweitzer,  L.B. Nikolskiy devoted  to  language  policy, were considered.Results and discussion. Language policy is a powerful tool of social control.  Due to the specifics   of  the  formation   of  a  unified  German  state,   it  is  possible   to  talk  about   a systematically  implemented  language  policy only from the  end of the  19th  century - the moment  the German  Empire was founded.  The current  position of the German  language in Germany is determined  by many extralinguistic factors, both diachronically (primarily by the  role  and  position  of the  Third Reich in world history) and  synchronically  (the  trend towards intensive cultural dialogue, openness of borders,  priority support for the rights of linguistic minorities).Conclusion. At   the   moment,    the   German   language   is   affected    by   the   values   of multiculturalism  and  pluralism cultivated in Europe  and  the  actively ongoing  process  of globalization. Recognizing the  importance  of the  German  language  in the  process  of the formation  of German cultural identity, the German government  is forced to focus primarily on  supporting  other  languages  and  dialects  common  in the  country.  The  question   of supporting and securing the German language as a state  language at the legislative level is still to be discussed.